Pemotongan Upah Tenaga Kerja di Pt Dewata Gassari Bali dalam Situasi Pandemi Covid 19 - Ida Bagus Ari Nugraha; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2022)
PT Dewata Gassari Bali enthroned at the Denpasar dam, held the same company color as the sale of LPG airflow. During Covid-19, it was seen that employers changed the regulations for giving fatigue medicine and alarms for work ahead of the rubber of their workers. The spread of COVID-19 has also resulted in a number of places visited decreasing so that the products marketed experience a drastic decline in sales. This results in a decrease in the price of goods marketed by certain companies. As a result of the losses suffered by the company, they made the decision to Termination of Employment (PHK) and Work from Home (WFH). This study aims to reveal the procedures for the implementation of payment of wages, protection of work status, and remuneration of workers at PT Dewata Gassari Bali. The method used in this analysis is institutional analysis which is empirically motivated by approaching reality and approaching the rule of law using a juridical approach. Sources of data in this study are primary data and secondary data. Data were analyzed by being collected, described and arranged descriptively and then systematized. The results of this study indicate that the cutting of fatigue medication and the dismissal of a number of employees are due to the company's finances being unstable